2019
DOI: 10.1017/s0031182019000544
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization ofEchinococcusisolates from various intermediate hosts in the Qinghai-Tibetan Plateau Area, China

Abstract: This study examined Echinococcus spp. genotypes and genetic variants isolated from humans as well as domestic and wild animals from the Qinghai-Tibetan Plateau Area using the cox1 gene. All samples except the pika isolates were identified as the Echinococcus granulosus sensu stricto. Sixteen different haplotypes with considerable intraspecific variation were detected and characterized in mitochondrial cox1 sequences. The parsimonious network of cox1 haplotypes showed star-like features, and the neutrality inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Among the included articles, most of the epidemiological investigations were concentrated in the northwestern region (91%; Table 2). The northwestern region was the main breeding area for sheep in China and was also a high-epidemic area for echinococcosis ( Han et al., 2019 ), among which Qinghai province has the highest prevalence rate ( Figure 3 ). From the perspective of geographic environment, the altitude subgroup analysis showed a relatively high prevalence of Echinococcus among sheep in high altitude areas, such as Qinghai province ( P < 0.05; Table S6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the included articles, most of the epidemiological investigations were concentrated in the northwestern region (91%; Table 2). The northwestern region was the main breeding area for sheep in China and was also a high-epidemic area for echinococcosis ( Han et al., 2019 ), among which Qinghai province has the highest prevalence rate ( Figure 3 ). From the perspective of geographic environment, the altitude subgroup analysis showed a relatively high prevalence of Echinococcus among sheep in high altitude areas, such as Qinghai province ( P < 0.05; Table S6 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was also, detected around Qinghai Lake in Ganzihe town of Haiyan County and Gonggongma village of Gangcha County towards the northeastern edge of the plateau. Until now, the diversity and population structure of E. shiquicus has been largely investigated by partial mitochondrial gene sequences of cox1 and/or nad1 (Ma et al, 2012(Ma et al, , 2015Wang et al, 2018;Han et al, 2019), and recently by mtDNA sequences of up to 2505 bp (Fan et al, 2016;Zhu et al, 2020). Moreover, studies have shown that by analysing longer DNA sequences or certain genes with higher resolution power, a better understanding of the intraspecies variation and phylogenetic resolution of Echinococcus species is realised (Laurimäe et al, 2018(Laurimäe et al, , 2019Ohiolei et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of E. shiquicus, progress has been made in understanding the genetic diversity and population structure, howbeit by short mitochondrial gene sequences of the cytochrome c oxidase subunit 1 (cox1) and the NADH dehydrogenase subunit 1 (nad1) (Ma et al, 2012(Ma et al, , 2015Wang et al, 2018;Han et al, 2019), with only a few studies employing longer mtDNA sequences (2505 bp) (Fan et al, 2016;Zhu et al, 2020). Meanwhile, a better insight into the population structure will require an extensive investigation across the plateau as conflicting population demographics/indices have so far been observed, which is either a consequence of short DNA sequences or sample size limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there are speculations that the speciation between both of them is a passive host transformation as a result of the evolution of their intermediate hosts, which eventually led to their ecological isolation and gave rise to 2 distinct species (Wang et al ., 2020 ; Wu et al ., 2021 ). Rodents, for instance, plateau pika ( Ochotona curzoniae ), the plateau vole ( Neodon fuscus ) and carnivorous' mammals, predominantly Tibetan foxes ( Vulpes ferrilata ) serve as intermediate and definitive hosts, respectively (Jiang et al ., 2012 ; Li et al ., 2018 , 2019 ; Han et al ., 2019 ). At present, E. shiquicus infection has been found in a variety of wild animals such as plateau pika, plateau vole, lacustrine vole ( Microtus limnophilus ), Blyth's mountain vole ( Phaiomys leucurus ) and Tibetan foxes in Sichuan Province, Qinghai Province, Tibet Autonomous Region, Gansu Province and other provinces/autonomous regions in the Qinghai-Tibet Plateau area, China (Boufana et al ., 2013 ; Fan et al ., 2016 ; Wang et al ., 2018 ; Weng et al ., 2020 ; Zhu et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%